Influence of malt source on beer chemistry, flavor, and flavor stability. (November 2018) - Bettenhausen, Harmonie M.; Barr, Lindsay; Broeckling, Corey D.; Chaparro, Jacqueline M.; Holbrook, Christian; Sedin, Dana; Heuberger, Adam L.
Abstract: Beverage quality in the brewing industry is heavily influenced by ingredient properties. The contribution of raw ingredients such as yeast and hops to beer flavor is well understood. However, the influence of barley genotype and/or environment on flavor (the malt 'source') is largely unexplored. Here, a study was performed to determine ( i ) if there are metabolite differences among six commercial malt sources, ( ii ) if differences in malt chemistry are reflected in the chemistry of the beer, and ( iii) if the differences in the beer chemistry impact sensory attributes of beer, through flavor and flavor stability. Six distinct sources of malts (six varieties from three maltsters) were brewed into six beers using a recipe designed to evaluate differences in flavor. Metabolomics and ionomics was used to characterize chemical variation among the six malts and beers using UHPLC- and HILIC-MS (non-volatile metabolites), HS-SPME/GC–MS (beer volatiles), and ICP-MS (malt metals). These analyses detected a total of 5042 compounds in malt, of which 217 were annotated and included amines, amino acids, fatty acids/lipids/fatty acyls, saccharides/glucosides/sugar acids/sugar alcohols, carboxylic acid derivatives, organic acids, phenolics/benzenoids, purines, pyrimidines/pyridines, terpenes, and organosulfurs. A total of 4568 compounds were detected in beer, of which 246 were annotated and included esters, aldehydes, and alcohols. Statistical analysis revealed chemical variation among the six malts (50/217 malt metabolites varied) and beers (150/246). The six beers were evaluated for flavor using a modified descriptive analysis for 45 sensory traits at 0, 4, and 8 weeks of storage at 4 °C. Principal component analysis of the sensory data revealed flavor differences among the six beers at 8 weeks, and the malt-type Full Pint was described as fruity and Meredith as corn chip . The metabolite and sensory data were integrated and revealed associations between flavor profiles in beer and the annotated malt and beer. The fruity or corn chip flavor profiles in beer were associated beer purines/pyrimidines, volatile ketones, amines, and phenolics, and malt lipids, saccharides, phenols, amines, and alkaloids. Taken together, these data support a role of malt source in beer flavor and flavor stability. As a raw ingredient, malting barley genotypes can be evaluated for a contribution to flavor, and this may be a future target for plant breeding, agronomy, and malting efforts to selectively improve flavor, flavor stability, and quality in beer. Abstract : Graphical abstract Highlights: Metabolite differences were discovered among six commercial malt sources. Variation in malt metabolites are reflected in the chemistry of the beer. Differences in beer metabolites impacted beer sensory through aging mechanisms.